Are Individual Microentrepreneurs who Intend to Grow Alert to Opportunities? - Jaci José Cenci; Hilka Pelizza Vier Machado; Carlos Eduardo Carvalho (BBR: Brazilian Business Review)
The aim of this paper is to identify the relationship between growth intentions and entrepreneurial alertness of individual microentrepreneurs (abbreviated as MEIs). The specific objectives are to test the multidimensionality of the construct entrepreneurial alertness and to verify whether there is a relationship between growth intentions and all other dimensions of alertness. The research method employed was a survey, which was carried out with 134 MEIs, and hypothesis testing on the multidimensionality of the construct alertness, which had empirical support, and on the relationship between growth intentions and entrepreneurial alertness, which was only partially supported by the empirical analysis. This research presents an original contribution to studies on the growth of microenterprises, a growing entrepreneurial category in Brazil. In addition, the present study presents a theoretical contribution to studies on the growth of small-sized businesses, as well as on entrepreneurial opportunities, emphasizing the existing relationship between growth intention and one dimension of entrepreneurial alertness.